Exudative lesions in diabetes mellitus - Horsfield, G. I. (1965)
Exudative lesions and capsular drops have been examined in a renal biopsy series of 25 diabetics and a post-mortem series of 100 consecutive diabetics. Electron microscopy of a capsular drop and an exudative lesion is described. Exudative lesions were found in 48% of the biopsies and 47% of the necropsy material. Capsular drops were found in 60% of the biopsies and 29% of the necropsy material. No correlation with age, proteinuria, hypertension, or uraemia was noted. The incidence of both types of lesion increased with the known duration of the diabetes.